The Use of Cone Beam Computed Tomography in Assessing the Insertion of Bone Conduction Hearing Implants - Calon, Tim George Ate; Johansson, Martin Lars; van den Burg, Elske Larissa; Janssen, Anna Maria Louisa; van Hoof, Marc; Stokroos, Robert Jan (Frontiers in Surgery, 2017)
Objective: This study aimed to compare post-operative Cone Beam CT (CBCT) imaging to Implant Stability Quotient (ISQ) measurement and direct caliper measurements as a suitable technique to assess Bone Conduction Hearing Implant (BCHI) seating and insertion depth. Methods: In vitro, BCHIs were completely (n=9) and partially inserted (n=9) in bone blocks of different densities and subsequently scanned. Scans were processed using 3DSlicer 4.3.1 and Mathematica 10.3. ISQ measurements were obtained for all BCHIs mounted with different abutment lengths (9 mm, 12 mm, 14 mm). CBCT imaging was performed for patients with a clinical indication. Results: In vitro, 95% prediction intervals for partially inserted and completely inserted BCHIs were determined. ISQ values significantly decreased with partial insertion, low-density artificial bone and longer abutment lengths. Evaluation of in vitro and in vivo 3D models allowed for assessment of insertion depth and inclination. Conclusion: CBCT imaging allows to study implant seating and insertion depth after BCHI surgery. This can be useful when visual confirmation is limited. It is possible to distinguish a partial BCHI insertion from a complete insertion in artificial bone blocks. This technique could prove to be a valuable research tool. In vitro, ISQ values for Ponto BCHIs relate to abutment length, insertion depth and artificial bone density.